PENGARUH RASIO-RASIO MODAL KERJA DAN ARUS KAS OPERASI TERHADAP PROFITABILITAS - Wahyuni, Marina Fitri; Saiful, Saiful; Nikmah, Nikmah (UNIB Press, 2017)
This study aimed is find an empirical evidence about the influence of working capital ratios and cash flow on profitability. Working capital ratios is proxied by the cash conversion cycle, current ratio, quick ratio, inventory turnover, accounts receivable turnover, turnover of debt and working capital turnover. Meanwhile cash flows dan profitability measured by change in cash flows and return on investment (ROI) respectively.Based on purposive sampling, 67 manufacturing companies were selected as a sample of this study for three years observation.This study found that the cash conversion cycle and quick ratio negatively influence on profitability. Incontrast, this study also found that current ratio positively influence on profitability. This study could not find the influence of inventory turnover, accounts receivable turnover, turnover of debt, working capital turnover, and operating cash flow on profitability.